Implementasi Pendidikan Karakter Dalam Pembelajaran Fiqih Santriwati Kelas 1 SMP Tahfidh Putri Al-Amien Prenduan - Tidjani, Afifah; Ida, Tolak (Jurnal Pendidikan Indonesia, 2022)
The rise of immoral cases among adolescents indicates a lack of character education. So that the world of education is expected to be a solution, especially in the world of Islamic boarding schools. One of them is through the learning of Islamic sciences such as Fiqh which is expected to be a "testament" to instill the values of character education. The problem raised in this study is the implementation of character education through fiqih learning, which is described in two focuses: 1. How to implement character education in Fiqih learning among grade 1 students of SMP Tahfidh Putri Al-Amien. 2. What are the supporting factors and obstacles to the implementation of character education in Fiqih learning among grade 1 students of SMP Tahfidh Putri Al-Amien. The methods used are interview, observation and documentation methods. From this method, the researcher then processes and analyzes to obtain data from respondents. For the validity of the data, researchers used triangulation between methods. Implementation of character education through Fiqh learning, namely by: a. The teacher uses the lecture method in delivering the material, b. Mentoring during practice sessions in class, c. Instilling exemplary qualities and habituations of good character with others. The inhibiting factors for the implementation of character education through Fiqh learning are: a. Some students lack concentration in following lessons, b. Weak ability to understand lessons for some students, and c. some teachers are unable to attend class.